“It’s Not Just Instagram Models”: Exploring the Gendered Political Potential of Young Women’s Instagram Use - Caldeira, Sofia P. (2021)
With over one billion monthly users worldwide (Constine, 2018) and being embedded in the everyday lives of many young people, Instagram has become a common topic of discussion both in popular media and scholarly debates. As young women are amongst the predominant active users of Instagram (WeAreSocial, 2019) and the demographic stereotypically associated with online self-representation (Burns, 2015), Instagram carries an underlying gendered political potential. This is manifested through online political practices such as hashtag activism (Highfield, 2016), as well as through Instagram’s use of user-generated content to challenge existing politics of representation, broadening the scope of who is considered photographable (Tiidenberg, 2018). This article explores how this gendered political potential is understood by young women using Instagram. This research is based on 13 in-depth interviews with a theoretical sample of female ‘ordinary’ Instagram users (i.e., not celebrities or Insta-famous), aged 18–35. Our findings illustrate how the perception of political potential is grounded in the participants’ understanding of Instagram as an aesthetically-oriented platform (Manovich, 2017). Most participants recognised the potential for engaging in visibility politics (Whittier, 2017), representing a wider diversity of femininities often absent from popular media. However, this was seen as tempered by the co-existence of idealised beauty conventions and the politics of popularity within social media (Van Dijck & Poell, 2013). Furthermore, this political potential is accompanied by the possibility of receiving backlash or being dismissed as a slacktivist (Glenn, 2015). As Instagram becomes a central part of contemporary visual cultures, this article seeks to critically explore the nuanced ways in which young women’s everyday experiences of Instagram intersect with broader cultural and political questions of gender representation.